THE ROLE OF THE METAVERSE IN THE FUTURE OF DIGITAL ARCHITECTURE: A SYSTEMATIC LITERATURE REVIEW AND RESEARCH PROSPECTS - E.M., Pramaesti,; J.A., Saraswati, (Soegijapranata Catholic University, 2025)
The emergence of the metaverse as a three-dimensional virtual space has significantly disrupted the paradigm of digital architecture, challenging the constraints of physical space and fostering the development of more immersive, interactive, and collaborative design approaches. However, conceptual disparities and methodological limitations persist in addressing the integration of this technology into architectural practice. This study aims to identify, categorize, and analyze academic literature on the relationship between the metaverse and digital architecture. The research employs a Systematic Literature Review (SLR) method using a structured approach, including inclusion and exclusion criteria, keyword search strategies, and content analysis from reputable scholarly sources. The data reviewed comprise literature from the past five years discussing metaverse architecture, digital design innovation, virtual environments, immersive technologies, and future architectural practices. The findings reveal that the metaverse offers the potential to redefine architectural design through user experience and spatial immersion—dimensions that remain underexplored in prior studies. This study also presents a research roadmap and recommendations for developing inclusive, collaborative, and sustainable metaverse design models for the future of digital architecture.